Future applications of advanced neonatal cerebral ultrasound. Issue 1 (January 2018) - de Goederen, R.; Vos, H.J.; de Jong, N.; Horsch, S.; Dudink, J.
Abstract: Ultrasound is a superb neonatal neuroimaging technique as it is non-invasive, easily accessible and safe. Ultrasound is still seen as complementary to other neonatal neuroimaging techniques (such as MRI) because it still lacks several important neuroimaging features such as quantitative tissue analysis. However, developments in ultrasound technology are predicted to follow each other in rapid succession and are expected to have a major impact on clinical neonatal cerebral ultrasound applications in the near future. Elastography, Ultrafast Doppler, Shear Wave imaging, Contrast Enhanced ultrasound and functional ultrasound are examples of techniques being discussed. The aim of this review is to provide a compact overview of current ultrasound developments which are likely to have an impact on neonatal cerebral ultrasound use.